Occupational use of high-level disinfectants and fecundity among nurses - Audrey J Gaskins; Jorge E Chavarro; Janet W Rich-Edwards; Stacey A Missmer; Francine Laden; Scott A Henn; Christina C Lawson (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVE: This study aimed to examine the relationship between occupational use of high-level disinfectants (HLD) and fecundity among female nurses. METHODS: Women currently employed outside the home and trying to get pregnant (N=1739) in the Nurses' Health Study 3 cohort (2010-2014) were included in this analysis. Occupational exposure to HLD used to disinfect medical instruments and use of protective equipment (PE) was self-reported on the baseline questionnaire. Every six months thereafter women reported the duration of their ongoing pregnancy attempt. Multivariable accelerated failure time models were used to estimate time ratios (TR) and 95% confidence intervals (95% CI). RESULTS: Nurses exposed to HLD prior to and at baseline had a 26% (95% CI 8-47%) and 12% (95% CI -2-28%) longer median duration of pregnancy attempt compared to nurses who were never exposed. Among nurses exposed at baseline to HLD, use of PE attenuated associations with fecundity impairments. Specifically, women using 0, 1, and ≥2 types of PE had 18% (95% CI -7-49%), 16% (95% -3-39%), and 0% (95% -22-28%) longer median durations of pregnancy attempt compared to women who were never exposed. While the use of PE varied greatly by type (9% for respiratory protection to 69% for protective gloves), use of each PE appeared to attenuate the associations of HLD exposure with reduced fecundity. CONCLUSION: Occupational use of HLD is associated with reduced fecundity among nurses, but use of PE appears to attenuate this risk.